Interaction between the effects of the selective estrogen modulator femarelle and a vitamin D analog in human umbilical artery vascular smooth muscle cells. Issue 174 (November 2017) - Somjen, Dalia; Knoll, Esther; Sharon, Orli; Many, Ariel; Stern, Naftali
Highlights: JKF increased ERα and decreased ERβ mRNA expression in pre-, post- and SaSO2 but not in male hObs. The binding of E2 only in female derived cells is competed by all the estrogens tested and is up-regulated by JKF. Treatment with F, D and E2 increased VDR and 1OHase mRNA expression and its activity in hObs, measured by 1, 25(OH)2D3 (1, 25D) production in female but not in male hObs. JKF modulated only the effects of E2 and D but not F in female hObs. These finding that the effects of F are independent of vitamin D levels in female-derived hObs may contribute to its beneficial role in treatment of post-menopausal bone loss. Abstract: To further investigate the interaction between vitamin D system and estrogen-mimetic compounds in the human vasculature we studied the effect of the "less- calcemic" analog of 1, 25(OH)2 D3 (1, 25D); JK 1624F2 -2 (JKF) in the presence of selective estrogen modulator femarelle (F), the phytoestrogen daidzein (D) and estradiol-17b (E2 ) on 3 [H] thymidine incorporation (DNA synthesis) and creatine kinase specific activity (CK) in human umbilical artery vascular smooth muscle cells (VSMC). F, D and E2, stimulated DNA synthesis at low concentrations, and inhibited it at high concentrations. All estrogen-related compounds increased CK dose- dependently. Daily treatment with JKF (1 nM for 3 days) resulted in decreased DNA synthesis, increased CK and up- regulation of the stimulation of DNA synthesis by low estrogen-related hormones whereas D- and E2 - mediated inhibition of cell proliferation was abolished by JKF. In contrast, inhibition of cell proliferation by F could not be blocked by JKF. JKF also up-regulated the stimulatory effects on CK by F, E2 and D. VSMC expressed Estrogen Receptor (ER)a and ERb mRNA at a relative ratio of 2.7:1.0, respectively. JKF pretreatment increased ERa (∼50%) and decreased ERb (∼25%) expression. E2 did not affect ERs whereas both D and F up-regulated ERb (∼100%) and ERa (∼50%). Additionally, JKF increased the intracellular competitive binding of F (from ∼70 to ∼310%), of D (from ∼60 to ∼250%) and of E2 from (from ∼ 70 to ∼320%). F reciprocally modulated the vitamin D system by up-regulating VDR- and 25 hydroxyy vitamin D 1-a hydroxylase (1OHase) mRNA expression (∼120%). F also stimulated 1OHase activity as indicated by an increase in the production of 1, 25D (∼250%). A similar increase was elicited by D (∼90%) but not by E2 . In conclusion, F has unique effects on human VSMC in that it can sustain inhibition of cell growth even in the presence of the vitamin D analog JKF. That JKF increases ER expression and F increased the endogenous production of 1, 25D and VDR expression offer new opportunities to modulate VSMC growth. Whether or not these mutual effects of F and JKF can be exploited to promote vascular health, particularly in estrogen-deficient states (e.g., menopause) is under investigation.